Reading In/Between: Migrant Bodies, Latin American Translations - Larkosh, Christopher (TTR : traduction, terminologie, rédaction)

(untitled) (Association canadienne de traductologie, 2004)
AbstractThis essay examines the role of translation in the redefinition of the relationship between authors and their respective national cultures, and in continuing discussions of gender, sexuality, migration and cultural identity in translation studies. The translation of Witold Gombrowicz’s novel Ferdydurke from Polish into Spanish by Cuban author Virgilio Piñera and a Translation Committee, not only calls into question the conventional dichotomy of author and translator, but also creates a transnational literary community which questions a number of assumptions about the history of translation in the West, its complicity both in the construction of literary canonicity and the maintenance of the educational institution.